A Quantitative Comparison of Mental Health Stigma Across Generation Z, Millennials, and Generation X in Davao del Sur - Camarillo, Johanna Marie R.; Betonio, Kyle Monique M.; Ortega, Precious Grace F.; Culajara, Claire Lynn B. (Yayasan Sinergi Kawula Muda, 2025)
Mental health stigma negatively impacts how individuals with mental health challenges are perceived and treated. This study explored generational differences in mental health stigma among Generation Z, Millennials, and Generation X (N=300; n=100 per group) using the Community Attitudes Toward Mentally Ill (CAMI) Scale and quota sampling for balanced representation. A descriptive-comparative design was applied, and data analysed using JAMOVI. The Shapiro-Wilk test confirmed normality (p= 102), allowing parametric testing. Results showed that Generation X had the highest stigma scores across all four CAMI subscales: Authoritarianism (M= 3.19), Benevolence (M= 2.56), Social Restrictiveness (M= 2.97), Community Mental Health Ideology (M= 2.72), while Millennials and Gen Z scored lower. These findings reflect a shift toward more open and accepting attitudes among younger generations. A one-way ANOVA revealed significant differences in stigma (Welch’s F= 16.00, p < .001), with post-hoc analysis confirming Generation X’s significantly higher stigma levels (p < .001). The study recommends generation-specific interventions: culturally sensitive, community-based programs for older adults, and digital, peer-driven strategies for younger groups. Future research should include broader generational representation and examine how culture, gender, and socioeconomic status influence stigma.